2013
DOI: 10.1002/oby.20458
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure assessment in severe obesity: Validation of a forearm approach

Abstract: Objective: Obesity is frequently associated with systemic hypertension. Blood pressure measure is inaccurate in severely obese patients because of poor cuff size fitting. Objective: The aim of the study is to assess the degree of agreement between the intra-arterial method as the gold standard vs. noninvasive methods, i.e., forearm blood pressure and upper-arm blood pressure measures. Design and Methods: A total of 1285 measures of intra-arterial and forearm blood pressure were taken in 51 severely obese patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Recently, Leblanc et al 20 compared NIBP measurements obtained from the upper arm and forearm of morbidly obese patients with intra-arterial control measurements from the contralateral arm. The investigators found that the NIBP measurements from both the upper arm and forearm locations resulted in SBP and DBP measurements that closely correlated with those obtained from the intra-arterial measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Leblanc et al 20 compared NIBP measurements obtained from the upper arm and forearm of morbidly obese patients with intra-arterial control measurements from the contralateral arm. The investigators found that the NIBP measurements from both the upper arm and forearm locations resulted in SBP and DBP measurements that closely correlated with those obtained from the intra-arterial measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 studies, 11,13 cuff types were compared (standard vs large, rigid cylindrical vs conical); in 3 studies, 4,17,21 blood pressure measurements obtained via direct intra-arterial vs ausculatory/oscillometric techniques were compared; and in 6 studies, [14][15][16][18][19][20] blood pressure measurements obtained from the upper arm versus the forearm were compared.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,18 When assessing blood pressure at alternative locations, it is essential to recognize that blood pressure varies appreciably in different parts of the arterial system, with SBP increasing in more distal arteries and DBP decreasinig. 23 Thus, because measurements of blood pressure in the forearm generally yield overestimates of SBP, DBP, and mean arterial pressure (MAP) compared with the upper arm (reported variances, 2.3-27 mm Hg), 10,14,[19][20][21]24,25 it is important to decide what discrepancy is clinically acceptable. 10,14,20 As McFarlane 10 described, a difference of ±5 mm Hg (standard deviation ≤8 mm Hg) is the standard used by the International Standards Organization and manufacturers that test noninvasive devices for measuring blood pressure against mercury sphygmo manometers.…”
Section: Mcfarlanementioning
confidence: 99%
“…In a majority of studies, recruiting young healthy adults and eliminating individual characteristics that might influence blood pressure measurements, such as known cardiac arrhythmias or unstable medical condition, controlled sample selection. [40][41][42][43][44] Pierin and colleagues, 42 Vinyoles and colleagues, 45 Schell and colleagues, 43,44,46,47 Domiano and colleagues, 48 and Leblanc and colleagues 49 reported participants classified as obese as defined by a BMI greater than 30 kg/m 2 ; however, only 1 study 49 reported participants classified as morbidly obese separately. In 2 studies 42,49 in which obesity was required for inclusion in the sample, comparison of the conclusions with individuals who are classified as normal weight is not attainable.…”
Section: Literature Analysismentioning
confidence: 95%